The Effect of Good Corporate Governance Implementation and Financial Policy on Tax Avoidance (Case Study in LQ45 Company Index) - Rangkuti, Maryam Monika; Manullang, Bintang Refenia (International Journal of Economics (IJEC), 2024)
The purpose of this study was to investigate potential correlations between Corporate Governance and Financial Policy on Tax Avoidance Practices. This investigation's primary goals and focus are companies that are listed in LQ45 Index for the 2020-2023 period. 70 observation samples in all were used in this study, and they were all chosen using purposive sampling methods. The data examined using SPSS software was subjected to multiple linear regression testing methodology for the  purposes  of  this  investigation.  The  use  of  GCG and leverage are  unrelated,  according  to  study  findings partially. Simultaneously, GCG and Leverage are related to Tax Avoidance Practice.